2015
DOI: 10.1139/cjfas-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Between-watershed movements of two anadromous salmonids in the Arctic

Abstract: A long-term study in the River Halselva in the Arctic region of Norway demonstrated that movements between watersheds were considerably higher in anadromous brown trout (Salmo trutta) than anadromous Arctic char (Salvelinus alpinus).Fourteen smolt year classes of both species were captured in a fish trap, individually tagged, and thereafter registered each time they passed the trap during their migration between the sea and fresh water every summer. Annual mean survival (i.e., recovery rate) after the first en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 42 publications
3
38
0
Order By: Relevance
“…Strikingly, while straying movement was detected in high proportions throughout the study area (especially in Nivelle and Nives), no genetic exchange that cannot be attributed to human‐mediated translocation was detected, suggesting that straying sea trout were not sexually mature, did not successfully reproduce, or, if they did so, their fitness was unexpectedly low. The former hypothesis would be in line with recent findings in North Atlantic showing that straying sea trout are more likely young and sexually immature (Jensen et al., ). Sea trout scale reading will possibly contribute to better understand straying behaviour in our river system.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Strikingly, while straying movement was detected in high proportions throughout the study area (especially in Nivelle and Nives), no genetic exchange that cannot be attributed to human‐mediated translocation was detected, suggesting that straying sea trout were not sexually mature, did not successfully reproduce, or, if they did so, their fitness was unexpectedly low. The former hypothesis would be in line with recent findings in North Atlantic showing that straying sea trout are more likely young and sexually immature (Jensen et al., ). Sea trout scale reading will possibly contribute to better understand straying behaviour in our river system.…”
Section: Discussionsupporting
confidence: 86%
“…Sea trout move frequently between river, estuary and sea habitats (Etheridge, Harrod, Bean, & Adams, 2008;Jensen et al, 2012;Pemberton, 1976;Pratten & Shearer, 1983b), and contrary to expectations, upstream movements are not always related to reproduction (King, Hillman, Elsmere, Stockley, & Stevens, 2016;Nall, 1930). Most sea trout individuals stay in seawater nearby their natal river mouth (Berg & Berg, 1987;Skrochowska, 1969b) but may also move to non-natal estuaries (Degerman, Leonardsson, & Lundqvist, 2012) and non-natal streams (Jensen, Diserud, Finstad, Fiske, & Rikardsen, 2015). The propensity to visit non-natal streams during marine migration (straying) appears to be more common among sea trout individuals originating from small streams (Degerman et al, 2012) or among those that have not reached sexual maturity (Jensen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Stock mixing and (or) straying has been documented in Arctic char (e.g., Moore et al 2013Moore et al , 2014Jensen et al 2015), including in the Cambridge Bay region (Dempson and Kristofferson 1987). The telemetry approach used in the present study, however, showed with a greater level of detail that stock mixing is extensive and occurs throughout the summer.…”
Section: Stock Mixing: Implications For Fishery Managementmentioning
confidence: 99%
“…In some populations, Arctic char forego marine migrations in the year before spawning (Gyselman 1994). Arctic char generally home to their natal system to spawn, but straying and stock mixing can be common (e.g., Dempson and Kristofferson 1987;Jensen et al 2015), especially in years when individuals do not spawn (Moore et al 2013(Moore et al , 2014. In some systems, spawning and overwintering sites are located in different areas, requiring a postspawning migration within fresh water (Johnson 1980;Beddow et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, runs of that size appear adequate to maintain viable populations of anadromous brown trout, as reported by Thomson and Lyndon (2018) from the Orkney, UK. Anadromous trout sometimes visit lower parts of rivers other than their home stream (Euzenat, 1999;Jensen et al, 2015;King et al, 2016;Masson et al, 2018;Solomon, 2006). The effective straying rate, however, may be low as immature first-time migrants tend to enter other streams more often than the mature veteran migrants do.…”
Section: Discussionmentioning
confidence: 99%